2011
DOI: 10.1111/j.1365-294x.2011.05199.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics highlights the role of bank vole metapopulation dynamics in the epidemiology of Puumala hantavirus

Abstract: Rodent host dynamics and dispersal are thought to be critical for hantavirus epidemiology as they determine pathogen persistence and transmission within and between host populations. We used landscape genetics to investigate how the population dynamics of the bank vole Myodes glareolus, the host of Puumala hantavirus (PUUV), vary with forest fragmentation and influence PUUV epidemiology. We sampled vole populations within the Ardennes, a French PUUV endemic area. We inferred demographic features such as popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 67 publications
6
78
0
Order By: Relevance
“…In the case of Southeast Asian rodents, one can imagine seasonal movements between flooded and non-flooded habitats, or between other habitats, but we lack data on these movements, which have not been the subject of publication to our knowledge. Because these movements may involve rodents infected with Leptospira , this process could have important consequences on Leptospira distributions within Southeast Asian agricultural landscapes (see [48] for an example of the importance of rodent movements for the epidemiology of a rodent-borne hantavirus in Europe). As has already been pointed out by Singleton and collaborators [49], more data is needed on the ecology of rodents in Southeast Asia, and such data would probably significantly increase our understanding of Leptospira epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Southeast Asian rodents, one can imagine seasonal movements between flooded and non-flooded habitats, or between other habitats, but we lack data on these movements, which have not been the subject of publication to our knowledge. Because these movements may involve rodents infected with Leptospira , this process could have important consequences on Leptospira distributions within Southeast Asian agricultural landscapes (see [48] for an example of the importance of rodent movements for the epidemiology of a rodent-borne hantavirus in Europe). As has already been pointed out by Singleton and collaborators [49], more data is needed on the ecology of rodents in Southeast Asia, and such data would probably significantly increase our understanding of Leptospira epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Ticks (268 questing Ixodes ricinus female ticks) and bank voles (72 Myodes glareolus ) were collected and trapped in the French Ardennes, an endemic region for rodent-borne hantaviruses, along a transect line of about 80 km in the course of a study of the epidemiology of Puumala hantavirus [16]. Along this transect, we sampled six sites in forested areas and four sites in fragmented habitats (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The mRNA levels of Mx2 genes were negatively correlated with PUUV loads in infected bank voles, corroborating the idea that Mx2 might limit PUUV replication in bank voles. They also showed that bank voles from forests (higher PUUV seroprevalence) had lower levels of Mx2 gene expression than voles living in fragmented hedge networks lower PUUV seroprevalence, higher genetic drift, see [110]. Again, these lower levels of expression may be considered to reflect tolerance mechanism against pathogens (including PUUV).…”
Section: Impact Of Immunity-related Genes On the Risk Of Hantavirumentioning
confidence: 99%